Pengaruh Kepemilikan Institusional Terhadap Penghindaran Pajak Perusahaan Manufaktur di Indonesia (2017-2019) - Wildan Dwi Lastyanto; Doddy Setiawan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
The purpose of this research was to determine the effect of institutional ownership on tax avoidance. The population in the study includes manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019 with a population of 193 companies. Determination of the number of samples using purposive sampling, in order to obtain a sample of 87 companies. The test hypothesis was carried out using multiple linear regression analysis techniques. Research result reports that institutional ownership had a significant and negative effect on tax avoidance. This finding means that in the context of agency theory, institutional investors tend to ignore the supervisory function, focus more on getting more benefits and encourage tax avoidance practices.